2.3k views
1 vote
Hi can someone help me with my question, which is 2 ( 3 + x) - 7 = x + 5?

2 Answers

4 votes

Answer:

x = 6

Explanation:

2(3+x)-7=x+5

We move all terms to the left:

2(3+x)-7-(x+5)=0

We add all the numbers together, and all the variables

2(x+3)-(x+5)-7=0

We multiply parentheses

2x-(x+5)+6-7=0

We get rid of parentheses

2x-x-5+6-7=0

We add all the numbers together, and all the variables

x-6=0

We move all terms containing x to the left, all other terms to the right

x=6

User Diganta Kumar
by
4.7k points
6 votes

Answer: x=6

Step-by-step explanation: Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation :

2*(3+x)-7-(x+5)=0

(2 • (x + 3) - 7) - (x + 5) = 0

x - 6 = 0

Solve : x-6 = 0

Add 6 to both sides of the equation :

x = 6

User Revanth Kumar
by
5.0k points